The nudging effect of AIGC labeling on users’ perceptions of automated news: evidence from EEG - Liu, Yuhan; Wang, Shuining; Yu, Guoming (Frontiers in Psychology, 2023)
Based on nudge theory and the social background of AI deep involvement in news production, this study primarily focuses on the impact of AIGC labeling cues on users’ perceptions of automated news. Specifically, a 2 (authorship disclosure nudge cues: with vs. without AIGC label) × 2 (automated news type: descriptive vs. evaluative news) within-subject experiment was carried out. Thirty-two participants were recruited to read automated news, evaluate the perceived content trustworthiness and be recorded with an EEG device. The results demonstrated that disclosure of AIGC labeling significantly reduced the trustworthiness perception of both fact-based descriptive and opinion-based evaluative news. In EEG, the delta PSD, theta PSD, alpha PSD and beta PSD with disclosure of AIGC labeling were significantly higher than those without AIGC labeling. Meanwhile, in descriptive news conditions, TAR with AIGC labeling was higher than that without AIGC labeling. These results suggested that AIGC labeling significantly improves the degree of attention concentration in reading and deepens the degree of cognitive processing. Users are nudged by AIGC labeling to shift their limited attention and cognitive resources to re-evaluating the information quality to obtain more prudent judgment results. This helps supplement the theoretical perspective on transparent disclosure nudging in the internet content governance research field and can offer practical guidance to use content labeling to regulate the media industry landscape in the face of AI’s pervasive presence.